Strengthening The Role Of Christian Family Education For The Faith Development Of Correctional Inmates In Correctional Institution - Rantung, Djoys A.; Jura , Demsy; Vandiano, Vardik (GoAcademica Research & Publishing, 2024)
Faith development is something very important in a person's life because through it, the level of spiritual maturity can be seen, which can have a positive influence on the life of every individual without exception. On that basis, the research title